2007
DOI: 10.1007/s00068-007-7093-6
|View full text |Cite
|
Sign up to set email alerts
|

Osteosynthesis of Proximal Humeral Fractures with the Fixed Angle PHILOS-plate

Abstract: In a retrospective study we analyzed the functional and radiological outcome of 30 proximal humeral fractures, treated by PHILOS-plate, a fixed-angle device. Two of them were characterized as type Neer III, 14 as type Neer IV, 5 as type Neer V and 9 as type Neer VI. There were 2 2-part, 16 3-part and 12 4-part fractures. According to the constant-score, the normalized constant-score and the UCLA-score, good to excellent results were obtained in 66.7, 76.7 and 76.7%. Twenty-six (86.7%) patients had no or mild p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
(63 reference statements)
2
17
0
Order By: Relevance
“…The average duration of the interval between the injury and time of surgery was 3.25 days whereas a study by Vijay et al; found the average time lag to be 6.24 days whereas Resch et al have found the interval between 2 to 10 days. 18,19 The average time for the radiological union in the present study was 13.5 weeks it was in accordance to similar studies done by Ebraheim et al, Klitscher et al Kilic et al [20][21][22] In the present study, 66.67% had excellent results and 16.67% had good results. Hirschmann et al, in their study with 64 patients with a minimum follow-up of four years, treated with locking plate, and have reported 75% excellent and good results.…”
Section: Discussionsupporting
confidence: 91%
“…The average duration of the interval between the injury and time of surgery was 3.25 days whereas a study by Vijay et al; found the average time lag to be 6.24 days whereas Resch et al have found the interval between 2 to 10 days. 18,19 The average time for the radiological union in the present study was 13.5 weeks it was in accordance to similar studies done by Ebraheim et al, Klitscher et al Kilic et al [20][21][22] In the present study, 66.67% had excellent results and 16.67% had good results. Hirschmann et al, in their study with 64 patients with a minimum follow-up of four years, treated with locking plate, and have reported 75% excellent and good results.…”
Section: Discussionsupporting
confidence: 91%
“…The mean neck/shaft angle after reduction was 133.7°and was never seen to change during later follow-ups. Examining all the angle values, we found 28 cases with consolidation at angles between 120°and 145°, which we considered within normal limits according to literature reports [2,7]. One patient (case 17) had an angle of 115°, a less than optimal reduction of tubercles, and a Constant score (CS) of 46.…”
Section: Surgical Techniquementioning
confidence: 98%
“…One last problem is vascularisation of the head, which is at risk, especially in 4-part fractures: the metaphyseal hinge distance is often less than 8 mm, and this is significant, due to interruption of the anterior circumflex artery, considered to be the most important for vascularisation of the humeral head [1,2], although several authors give more importance to the posterior circumflex artery [3]. We therefore believe that 3-part fractures have favourable prognosis and should be clearly distinguished, in assessments, from those with 4 parts.…”
Section: Surgical Techniquementioning
confidence: 99%
See 2 more Smart Citations